Genomic targeting and mapping of a gametocidal gene in wheat - See, Deven R. (Kansas State University, 2007)
Segregation distortion describes the transmission of an allele or alleles of a heterozygous locus at a higher frequency than expected in a Mendelian ratio. From the organism's view, segregation distortion is the preferential retention of chromosomal blocks carrying genes beneficial to its fitness and reproductive viability. In wheat the best studied segregation distortes are those introduced from Aegilops species; these selfish genetic elements are named gametocidal (Gc) genes and the chromosomes carrying them are called Gc chromosomes. This genetic mechanism causes chromosome breakage in gametophytes lacking the Gc carrier chromosome, thus favoring its own retention in the genome. While the mode of action of the Gc genes is not yet known, they have been used extensively in wheat genetics for the development of deletion stocks, a key resource for elucidating the structure of physical regions containing important genes. The objective of this study was to develop the tools necessary to map the Gc2 gene derived from Ae. sharonensis and perform map-based cloning. Extensive physical and genetic mapping located the gametocidal gene on the distal 1% of the 4BL arm present in the T4BS[dot in middle of line]4BL-4S[sh superscript]#1L translocation chromosome. Comparative genomics using rice provided markers distal and proximal to the Gc2 locus; however, synteny broke down at the locus. The characterization of this chromosomal region has provided insight into its recombination frequency, synteny and composition; however, the dynamic architecture of the end of the chromosome has made comparative mapping of this region difficult.
Keywords: Wheat; Gametocidal gene; Aegilops sharonensis; Triticum aestivum; Biology, Genetics (0369)